2005
DOI: 10.1074/jbc.m414017200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species Sequence Analysis Reveals Multiple Charged Residue-rich Domains That Regulate Nuclear/Cytoplasmic Partitioning and Membrane Localization of A Kinase Anchoring Protein 12 (SSeCKS/Gravin)

Abstract: A kinase anchoring proteins (AKAPs) assemble and compartmentalize multiprotein signaling complexes at discrete subcellular locales and thus confer specificity to transduction cascades using ubiquitous signaling enzymes, such as protein kinase A. Intrinsic targeting domains in each AKAP determine the subcellular localization of these complexes and, along with protein-protein interaction domains, form the core of AKAP function. As a foundational step toward elucidating the relationship between location and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…Also, both human and zebrafish Gravin localized to distinct peripheral membrane puncta as was reported previously for human Gravin (Fig. 2C, white arrows; Streb and Miano 2005). Using a membrane-localized RFP as a control, we determined that these puncta are due to concentrated Gravin and not just artifacts of the fixation (data not shown).…”
Section: Zebrafish Gravin Promotes Cell Shape Changes In Mammalian Cellsmentioning
confidence: 48%
See 1 more Smart Citation
“…Also, both human and zebrafish Gravin localized to distinct peripheral membrane puncta as was reported previously for human Gravin (Fig. 2C, white arrows; Streb and Miano 2005). Using a membrane-localized RFP as a control, we determined that these puncta are due to concentrated Gravin and not just artifacts of the fixation (data not shown).…”
Section: Zebrafish Gravin Promotes Cell Shape Changes In Mammalian Cellsmentioning
confidence: 48%
“…The most highly conserved domains of Gravin are three short basic regions, which are implicated in reversible electrostatic interactions with the plasma membrane (Fig. 1B;Streb and Miano 2005).…”
Section: Gravin Is Expressed During Early Zebrafish Developmentmentioning
confidence: 99%
“…Here we demonstrate that hypoxia, or more specifically HIF-1's ability to differentially bind to AKAP12v2 vs. AKAP12v1, is a transcriptional regulator of AKAP12v2. Previous work examining exogenous expression of the AKAP12 isoforms and deletion constructs in COS7 cells showed that the coding sequence difference between variants could account for the different subcellular localizations, including: nuclear/cytoplasmic and perinuclear/cell periphery (20,23). Our modeling studies indicate that the main difference between AKAP12v1 and AKAP12v2 is the myristoylation site that exists at the N-terminal region of AKAP12v1 (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…CpG islands can be located in different positions of genes, and differential methylation can be observed in any of these CpG islands (20). A report recently revealed that the 5'-flanking sequence from -1,034 to +1 is important in AKAP12α transcription by performing promoter analysis of the AKAP12α gene in NIH-3TS cells (21). Thus, we investigated whether the AKAP12α promoter has CpG islands that are methylated by DNMTs.…”
Section: Discussionmentioning
confidence: 99%